2018
DOI: 10.1038/s41598-018-31489-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mutations in the Mitochondrial Encoded Electron Transport Chain Complexes in Acute Myeloid Leukemia

Abstract: Acute Myeloid Leukemia is a devastating and heterogeneous, hematological malignancy characterized by the uncontrolled proliferation of undifferentiated myeloid progenitor cells—blasts. Mutations in certain mitochondrial proteins, such as IDH2 have been shown to contribute to leukemogenesis. However, the role of mutations in mitochondrial-encoded Electron Transport Chain (ETC) genes have thus far not been well elucidated in AML. Here, we use TCGA data to characterize mutations in the ETC genes and their associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 38 publications
0
37
1
Order By: Relevance
“…Overall survival analysis showed no differences among patients carrying a high versus low mtDNA mutational burden in tumors, which is in contrast with the data reported in breast cancer (28). A high mtDNA mutational burden has been associated with a worse outcome in pulmonary adenocarcinoma, acute myeloid leukemia, and pancreatic ductal adenocarcinoma (18,111,112); the opposite was observed in oral squamous cell carcinoma, and even acute myeloid leukemia, and breast cancer (28,113,114). We cannot exclude potential bias due to the nature of the studied mutations, the clinical characteristics of the patients included, or the ethnic/genetic background of the populations studied.…”
Section: Mtdna Mutations and Clinical Relevancecontrasting
confidence: 83%
See 2 more Smart Citations
“…Overall survival analysis showed no differences among patients carrying a high versus low mtDNA mutational burden in tumors, which is in contrast with the data reported in breast cancer (28). A high mtDNA mutational burden has been associated with a worse outcome in pulmonary adenocarcinoma, acute myeloid leukemia, and pancreatic ductal adenocarcinoma (18,111,112); the opposite was observed in oral squamous cell carcinoma, and even acute myeloid leukemia, and breast cancer (28,113,114). We cannot exclude potential bias due to the nature of the studied mutations, the clinical characteristics of the patients included, or the ethnic/genetic background of the populations studied.…”
Section: Mtdna Mutations and Clinical Relevancecontrasting
confidence: 83%
“…Our small sample size and potential population stratification, since all patients were recruited in Mexico City, might also bias our results. As well, we cannot ignore the fact that other alterations, such as the mtDNA-CN (suggested as a potential prognostic biomarker for breast cancer), mito epigenetic processes, and nuclear genes that are involved in the mitochondrial biogenesis, may be clinically relevant (18,71,115,116). Thus, studies are necessary for larger cohorts of patients to determine the significance of the mtDNA mutational burden as a biomarker in breast cancer.…”
Section: Mtdna Mutations and Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Because Warburg also observed increased aerobic glycolysis in normal proliferating cells and noted that it was reversible under normal conditions, he postulated that aerobic glycolysis was a consequence of irreversible damage to respiration in tumors (Warburg et al, 1924). Although later studies found mutations in some mitochondrial DNA-encoded ETC genes and genomic DNA-encoded genes of the TCA cycle (Baysal et al, 2000;Ward et al, 2010;Wu, Akhtari, & Alachkar, 2018), damaged respiration as an intrinsic property or "origin" of cancer is not established ( Ju et al, 2014;Stewart et al, 2015). In addition, hypoxia has long been known to stimulate glycolytic metabolism (Semenza, 2012).…”
Section: The Glycolytic Phenotypementioning
confidence: 99%
“…This has been cited as a justification for the development mitochondria-targeting compounds (14,15). Drugs targeting many other aspects of mitochondrial biology, such as the generation of reactive oxygen species, the electron transport chain, or the mitochondrial permeability transition pore have also been shown to kill tumor cells (16)(17)(18)(19)(20)(21)(22). "Mitocan" has been proposed as a generalized term for Abbreviations:…”
Section: Introductionmentioning
confidence: 99%